2019
DOI: 10.14720/aas.2019.114.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium toxicity in African yam bean (Sphenostylis stenocarpa (HOCHST. EX A.RICH.) HARMS genotypes

Abstract: Cadmium toxicity in African yam bean (Sphenostylis stenocarpa) (Hochst. ex A.Rich.) Harms genotypesAbstract: The aim of the study was to investigate the growth responses of African yam bean (Sphenostylis sternocarpa (Hochst. ex A. Rich.) Harms (AYB) to cadmium pollution. Top garden soil (0 -10 cm) was obtained as pooled and polluted with cadmium (as CdCl 2 ) at the rate of 12 mg kg -1 , which is equivalent to 3 times the ecotoxicological screening value of Cd. The polluted soils were made ready for use 3 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…It was reported that the tubers can be cooked and eaten in the same manner with other tubers like yams and potatoes. The flavor of the tuber is similar to that of potatoes (Olisa et al, 2010;Okoye et al, 2019). The colour of the seed may differ from creamywhite or brownish-yellow to dark brown, occasionally with black steaky appearance.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…It was reported that the tubers can be cooked and eaten in the same manner with other tubers like yams and potatoes. The flavor of the tuber is similar to that of potatoes (Olisa et al, 2010;Okoye et al, 2019). The colour of the seed may differ from creamywhite or brownish-yellow to dark brown, occasionally with black steaky appearance.…”
Section: Introductionmentioning
confidence: 79%
“…Ikemefuna and Julian, 2010). AYB plant yields small spindle-figured tubers that are about 5.0 to 7.5 cm tall (Olisa et al, 2010;Okoye et al, 2019;Aremu and Ibirinde, 2012). The seeds are usually ground and substituted to other flour to produce composite flour so as to improve its functional potentials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The crop tubers can be roasted, fried, or cooked and eaten such as yam and potato. The tuber flavor is like that of potatoes [62]. The tubers from Africa yam bean can be store for a longer period without any form of spoilage due to microbial action as a result of its low moisture content of about 10.3% [44].…”
Section: Potential Of Africa Yam Bean Toward Food Security and Sustainabilitymentioning
confidence: 99%